'One tooth one child': evaluating the effects of diet and fertility on the oral health of women from archaeological sites in South America. (16th November 2018) - Carvalho, Maria Rita G.; Pezo‐Lanfranco, Luis; Eggers, Sabine
Abstract : Women from ancient societies have shown a higher prevalence of dental caries in comparison with men. Recent research has shown that the relationship between increased oestrogen production during pregnancy and decreased salivary flow is a possible cause for the higher levels of caries in women, which is in contrast to the traditional view of sexual division of labour resulting in unequal access to cariogenic food. In order to test these two hypotheses, individuals exhumed from 12 South American archaeological sites were examined for markers of oral health (caries, ante mortem tooth loss, deep caries, and enamel hypoplasia) and compared in terms of fertility (Crude Birth Rate) and subsistence systems. Our results suggest that diet and other cultural practices remain the most important factors affecting oral health and that the effects of hormones can be masked by them. Such findings add to the discussion regarding the availability of micronutrients in such societies affecting caries experience in pregnant women, because of their special nutritional requirements.